KARAKTER POPULASI IKAN PUNTUNG ANYUT (Balantheocheilos melanopterus) DI SUNGAI MUSI MENGGUNAKAN ANALISIS MORFOMETRIK - Ni’am Muflikah; Arif Wibowo (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The objectives of this research were to identify population character of balashark fish in Musi River base on morphometric character and to determine which were the main predictor as morphometric characters.This research was conducted in 2007 in Musi River South Sumatra Province. Samples were selected base on purposive sampling method, at sum 45 specimens for morphometric observation. Measurements were made on 22 morphometric characters on the left side of body. Morphometric data were subject to PCA (Principal Component Analysis) and Discriminate Analysis using Statistic version 6.0 softwareThe result showed base on morphometric character analysis of balashark population in Musi River, there were three different subpopulations as reference of unit management of balashark fishes in Musi River. As the main character predictor among the groups (subpopulation/group 1, 2 and 3) are IOW (Inter Orbital Width/22), DFL (Dorsal Fin Length/7) and PDL (Peduncle Length/4). First group (Group 1) has longest similiarty distance (most difference group) compared with others subpopulation (Group 2 and Group 3).